The Impact of Raising Alcohol Taxes on Government Tax Revenue: Insights from Five European Countries - Jakob Manthey; Inese Gobiņa; Laura Isajeva; Jarosław Neneman; Rainer Reile; Mindaugas Štelemėkas; Jürgen Rehm (Applied Health Economics and Health Policy, 2024)
Abstract Background and Objective Reducing the affordability of alcoholic beverages by increasing alcohol excise taxation can lead to a reduction in alcohol consumption but the impact on government alcohol excise tax revenue is poorly understood. This study aimed to (a) describe cross-country tax revenue variations and (b) investigate how changes in taxation were related to changes in government tax revenue, using data from Estonia, Germany, Latvia, Lithuania and Poland. Methods For the population aged 15 years or older, we calculated the annual per capita alcohol excise tax revenue, total tax revenue, gross domestic product and alcohol consumption. In addition to descriptive analyses, joinpoint regressions were performed to identify whether changes in alcohol excise taxation were linked to changes in alcohol excise revenue since 1999. Results In 2022, the per capita alcohol excise tax revenue was lowest in Germany ( exteuro44.2) and highest in Estonia ( exteuro218.4). In all countries, the alcohol excise tax revenue was mostly determined by spirit sales (57–72% of total alcohol tax revenue). During 2010–20, inflation-adjusted per capita alcohol excise tax revenues have declined in Germany (-0.167em22.9%), Poland (-0.167em19.1%) and Estonia (-0.167em4.2%) and increased in Latvia (+0.167em56.8%) and Lithuania (+0.167em49.3%). In periods of policy non-action, alcohol consumption and tax revenue showed similar trends, but tax level increases were accompanied by increased revenue and stagnant or decreased consumption. Conclusions Increasing alcohol taxation was not linked to decreased but increased government revenue. Policymakers can increase revenue and reduce alcohol consumption and harm by increasing alcohol taxes.
Keywords: 330